2010
DOI: 10.1080/08927010903216572
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of biofilm formation on titanium surfaces modified with conjugated molecules comprised of antimicrobial and titanium-binding peptides

Abstract: Specific binding of antimicrobial peptides to titanium surfaces may serve to prevent biofilm formation, leading to a reduction in peri-implantitis. This study evaluated the binding behavior of conjugated molecules consisting of antimicrobial and hexapeptidic titanium-binding peptides

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
76
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 101 publications
(76 citation statements)
references
References 39 publications
0
76
0
Order By: Relevance
“…Hauser-Gerspach et al reported that release of F ions from resin composites decreased bacterial adhesion 25) . In earlier studies, we demonstrated a number of mechanisms capable of inhibiting biofilm accumulation on a Ti surface: coating with alumina for inhibition of initial attachment 21) , application of F + -implantation 33) and immobilization of anti-microbial peptides 42) . Such surface modification may also prove to be effective on TZP surfaces.…”
Section: Discussionmentioning
confidence: 99%
“…Hauser-Gerspach et al reported that release of F ions from resin composites decreased bacterial adhesion 25) . In earlier studies, we demonstrated a number of mechanisms capable of inhibiting biofilm accumulation on a Ti surface: coating with alumina for inhibition of initial attachment 21) , application of F + -implantation 33) and immobilization of anti-microbial peptides 42) . Such surface modification may also prove to be effective on TZP surfaces.…”
Section: Discussionmentioning
confidence: 99%
“…33,[36][37][38] Yoshinari et al reported that the modification of Ti surface with titaniumbinding peptides (minTBP-1) and lactoferricin showed a reduction in the bioactivity of P. gingivalis. 39 Although the antibacterial mechanism of LF on gram-positive pathogens is still not well understood, the interaction between LF and the cell membrane of gram-positive bacteria has been reported. Leitch et al reported that LF binds to lipoteichoic acid (LTA), which is a component of nearly all grampositive membranes and increases the permeability of lysozyme causing the release of LTA from the cell surface.…”
Section: B Inhibition Of S Gordonii Adhesion and The Bactericidal Ementioning
confidence: 99%
“…In vitro antimicrobial studies have found that a GL13K peptide coating is bactericidal and inhibits biofilm growth for pathogens related to peri-implantitis, such as P. gingivalis, S. gordonii and P. aeruginosa under static growth conditions 142,155) . Furthermore, AMP surfaces displayed antimicrobial activity under dynamic growth conditions against S. gordonii 156) and under static growth conditions against Streptococcus mutans, Staphylococcus epidermidis and Escherichia coli 159) .…”
Section: Antimicrobial Peptide Surfacesmentioning
confidence: 99%